Nickel immobilization in ceramic matrix admixed with waste nickel hydroxide - Osińska, Malgorzata (Waste management (New York, N.Y.), 2003)
WAXS examinations performed with nickel hydroxide samples heated to various temperatures showed that freshly settled wet nickel hydroxide sample contains some amount of crystalline beta-Ni(OH)(2) structure and its share increased when sample was dried during 3 weeks at ambient temperature. However, the share significantly decreased when the sample was dried at 110 degrees C and more so at 250 degrees C. Crystalline phase traces of Ni(OH)(2) disappeared after sample burning at 980 degrees C and instead the distinct presence of crystalline NiO was determined. The above samples were examined for solubility in stoichiometric amount of sulphuric acid diluted with water to pH 1.9 and 2.8. Solubility was determined by measuring nickel ion concentration in leachate by the AAS method. The dissolving rate was found to decrease with the rise of temperature to which the nickel hydroxide samples were heated. The solubility of Ni(OH)(2) sample burnt at 980 degrees C was undetectable during 90 h solubility-testing time likely due to its transformation into sparingly soluble crystalline NiO. The latter is considered to be the reason for effective immobilization of waste nickel hydroxide in ceramic prepared by blending with clay and sintering at 980 degrees C